2021
DOI: 10.1109/access.2021.3085349
|View full text |Cite
|
Sign up to set email alerts
|

One-Sided and Two One-Sided Multivariate Homogeneously Weighted Moving Charts for Monitoring Process Mean

Abstract: Multivariate memory-type control charts that use information from both the current and previous process observations have been proposed. They are designed to detect shifts in both upper and downward directions with equal precision when monitoring the process mean vector. The absence of directional sensitivity can limit the charts' application, particularly when users are interested in detecting variations in one direction than the other. This article proposes one-sided and two one-sided multivariate control ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Malela-Majika et al [35] corrected the variance used in the HHWMA X chart design proposed by [51]. For more details regarding the parametric DHWMA and HWMA charts for monitoring the location parameter, readers are referred to Alevizakos et al [22,23,56,65].…”
Section: Joint Location and Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Malela-Majika et al [35] corrected the variance used in the HHWMA X chart design proposed by [51]. For more details regarding the parametric DHWMA and HWMA charts for monitoring the location parameter, readers are referred to Alevizakos et al [22,23,56,65].…”
Section: Joint Location and Scalementioning
confidence: 99%
“…Their performance analysis revealed that the MHWMA T 2 chart outperforms its multivariate counterparts under known and estimated process parameters. Later, Adegoke et al [56] proposed one and two one-sided MHWMA charts for monitoring small shifts in the process mean vector, denoted as the OMHWMAI and OMHWMAII, respectively. The OMHWMAI chart is a one-sided chart for monitoring upward shifts by transforming the observation X i into positive values.…”
Section: Locationmentioning
confidence: 99%
“…Control schemes have been frequently used for fault detection in quality control with products and health-care monitoring [10][11][12][13][14]. A process should be monitored using statistical means to determine whether a shift occurs, and action should be taken once the process is considered out-of-control (OC) [15][16][17][18]. Many researchers have discussed and proposed many useful charts, such as Shewhart charts [19,20], cumulative sum (CUSUM) charts [21][22][23][24][25][26][27][28][29][30], and exponentially weighted moving average (EWMA) charts [31][32][33][34][35][36][37][38], to detect whether there is a change in quality characteristics in a process.…”
Section: Introductionmentioning
confidence: 99%